2019
DOI: 10.3390/mi11010019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nanocapsules on Red Blood Cells Interplay Jointly Assessed by Optical Tweezers and Microscopy

Abstract: In the framework of novel medical paradigm the red blood cells (RBCs) have a great potential to be used as drug delivery carriers. This approach requires an ultimate understanding of the peculiarities of mutual interaction of RBC influenced by nano-materials composed the drugs. Optical tweezers (OT) is widely used to explore mechanisms of cells’ interaction with the ability to trap non-invasively, manipulate and displace living cells with a notably high accuracy. In the current study, the mutual interaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Except that, Avsievich et al exploited a two-channel optical tweezer system to investigate the mutual interaction of RBC with polymeric nano-capsules (NCs). The results suggest that in the presence of NCs, the deformation and aggregation of RBCs satisfy the "cross-bridges" model in plasma, which might provide new insights to investigate the effects of NCs on the RBC interaction and estimate the possible cytoxic effects [97]. Besides, Sheikh-Hasani et al used optical tweezers to measure the viscoelastic properties of human RBCs that were treated by statin drugs [98].…”
Section: Optical Deformation Of Rbcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except that, Avsievich et al exploited a two-channel optical tweezer system to investigate the mutual interaction of RBC with polymeric nano-capsules (NCs). The results suggest that in the presence of NCs, the deformation and aggregation of RBCs satisfy the "cross-bridges" model in plasma, which might provide new insights to investigate the effects of NCs on the RBC interaction and estimate the possible cytoxic effects [97]. Besides, Sheikh-Hasani et al used optical tweezers to measure the viscoelastic properties of human RBCs that were treated by statin drugs [98].…”
Section: Optical Deformation Of Rbcsmentioning
confidence: 99%
“…Furthermore, the possible side effects of nanocarriers could be revealed through the optical tweezers at a single-cell level, thus bringing new insights to improve their biocompatibility. Avsievich et al used optical tweezer to evaluate the RBC response to four kinds of NCs in terms of RBC aggregation in autologous plasma [97]. They found that the magnetite and rhodamine-labeled NCs are prone to strong agglomeration in plasma, while secondary antibody and RNA-NCs are relatively stable and uniformly distributed.…”
Section: Optical Aggregation Of Rbcsmentioning
confidence: 99%
“…The role of macromolecule absorption in altering RBC mechanical properties and hence in influencing aggregation dynamics has been studied in detail with the same HOTs integrated with a fluorescence microscopy [150]. Recent works from our group have visualized the membrane morphologies of RBCs that adhered to each other by scanning electron microscopy (SEM) as shown in Figure 12 and evaluated the adhering strength in dextran solutions of different molecular weights (70 kDa, 150 kDa and 500 kDa) by conventional dual-beam OTs [151,152]. The SEM visualization of RBCs in mutual interactions has enabled the direct observation of the cilia on the cell surface, and the calculated cilia density is in good agreement with the deduced cross-bridges density in the "cross-bridging" model.…”
Section: Evaluation Of Dynamic Cell-cell Interaction Between Rbcsmentioning
confidence: 99%
“…[4][5][6] During the last few decades, a novel laser-based non-invasive technique, optical tweezers (OTs), has been developed into a popular method in living cell analytical studies, which enables precise manipulation and detection of bio-forces simultaneously. [7][8][9] The interactions of light with biological tissue through different mechanisms, including photo-thermal actions, photochemical reactions, and photobiomodulation, can elicit stimulatory and inhibitory effects on tissue conditions, depending on the preset light parameters, thus have been drastically investigated. 10 Tremendous valuable results have been obtained, especially after the invention and development of laser technology.…”
Section: Introductionmentioning
confidence: 99%